Academization Forms of Popular Music - Yakovlev, Oleksandr; Levko, Veronika (Journal of History Culture and Art Research, 2020)
The paper reveals the issues of the academization of popular music in the contemporary cultural space. Already in the 19th century, there were frequent phenomena of the transformation of everyday popular genres, which, thanks to composer intervention, changed their status from applied music to presented (autonomous). In the 20th century, the transformation process has reached a new level, and today we can talk about the academization of popular music as one of the specific phenomena of the 21st century musical culture. The academization of popular music becomes possible in cases where the composition is a highly artistic work that has semantic content, expressed in the presence of several cultural codes; it has passed the test of time, thanks to which its true value was determined; the composition in the process of rethinking was adapted to the standards of academic music in terms of instrumentation, developmental techniques, and musical forms, which ultimately changed the forms of its existence and included it in modern concert academic practice. Academization is characteristic of all cultures, where academic music is part of the national cultural tradition. One of the striking examples of the academization of popular music is the treatment of contemporary Ukrainian academic composer V. Stepurko popular songs by B. Vesolovsky and A. Kos-Anatolsky of the 1930s – 1960s, which returned to the concert stage decades later not as entertaining music, but as part of the cultural heritage of the 20th century.